A Proposed Model for Measuring Social Responsibility and Its Application in Jordanian Business Environment - Al-Haziameh, Amer; Bataineh, Rafat; Zureigat, Bilal (International Journal of Supply Chain Management, 2020)
Abstract This study examines the extent of corporate social responsibility practices amongst listed Jordanian companies at Amman Stock Exchange (ASE). corporate social responsibility   had been measured in this study using a corporate social responsibility disclosure index  and which encompasses  four groups. 53 Jordanian companies examined during the period 2016-2018. The finding reveals that Jordanian companies adopt corporate social responsibility on different types of information including  employee information, environment information, society information and customer information, although this corporate social responsibility disclosure might be considered low as the means of disclosure were (52.2%). More specifically, the mean disclosure for employee information, environment information, society information and customer information were (50%), (40.9%),(39.1%) and (95.5%), respectively.  In addition, the results show that the highest corporate social responsibility disclosure was for the customer information and the lowest was for the society information.